Keterlibatan High Involvement Management untuk Menjamin Kualitas Manajemen Sumber Daya Manusia - Samsudin, Acep; Prabowo, Budi; Sari, Fatimah Salsa Biela; Khoirunnisa, Maulidya; Permana, Berlian Dewa Prawisuda (Ikatan Da'i Indonesia, 2024)
Studies on human resource management (HRM) have been supported by previous research that there are best practices, high-involvement management (HIM) that can guarantee superior organizational performance. However, there are still concerns that contingency theory still applies, namely that the fit between the human resource system and its context, and in particular the organization's business strategy, is important, and thus, High-Involvement Management (HIM) will only outperform other systems in certain circumstances. In the 1990s, there was a spate of research that attempted to test whether High-Involvement Management (HIM) was indeed universally relevant. This journal reviews these studies. This journal first introduces the conceptual dimensions of HRM and performance. This suggests that the issues are more than a simple competition between universalism and contingency theory. There are more complex hypotheses linking human resource practices beneath the surface of the current literature. This journal reviews research based on these hypotheses, and shows that the studies provide an uneven picture. First, there are conceptual differences underlying the studies and, second, the results vary across studies, and the effects of High-Involvement Management (HIM) vary across performance measures, even within particular studies. Although quite a number of studies claim to support universalism, their claims are not always unequivocally supported by their research evidence, and it is premature to conclude that they support universalism. There is more support for the 'lean production' argument which emphasizes the interaction effect between DIA and total quality management on performance.